Volume 3: Heat Transfer; Electric Power; Industrial and Cogeneration 1999
DOI: 10.1115/99-gt-261
|View full text |Cite
|
Sign up to set email alerts
|

Highly Turbulent Mainstream Effects on Film Cooling of a Simulated Airfoil Leading Edge

Abstract: The influence of a high mainstream turbulence was examined in an experimental study of film cooling on a simulated turbine blade leading edge. Detailed heat transfer coefficient and adiabatic effectiveness values were measured under conditions representative of actual environments in a gas turbine engine. The two parameters were also combined for a net heat flux reduction analysis. Turbulence levels of Tu = 17% were achieved by modifying a cross-jets turbulence generator with a large cylinder element. A quarte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Since one of the purposes of the present study was to compare the computational prediction of heat transfer coefficients with experimental data, the geometry of the leading edge used in these simulations was identical to the computational study carried out by Dobrowolski et al (2009) and as close as possible to the physical model employed by Yuki et al (1998) and Johnston et al (1999). However it should be pointed out that these studies had a quarter circle model with a suction slot on the bottom whereas the present study used a half cylinder model.…”
Section: Description Of the Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Since one of the purposes of the present study was to compare the computational prediction of heat transfer coefficients with experimental data, the geometry of the leading edge used in these simulations was identical to the computational study carried out by Dobrowolski et al (2009) and as close as possible to the physical model employed by Yuki et al (1998) and Johnston et al (1999). However it should be pointed out that these studies had a quarter circle model with a suction slot on the bottom whereas the present study used a half cylinder model.…”
Section: Description Of the Modelmentioning
confidence: 99%
“…In this section, computational predictions of the heat transfer coefficient augmentation were compared with experimental data from Yuki et al (1998) and Johnston et al (1999) because these studies are the only experimental data that had the same commonly used round hole configuration. However it should be acknowledged that their model was not a full leading edge thus this was not a perfect comparison.…”
Section: Comparison Of Heat Transfer Coefficient Augmentation Predictmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors such as the film cooling blowing rate, freestream turbulence level and curvature will have a large effect on the results. This is evidenced by the ratios of film DATA ANALYSIS AND RESULTS cooled heat transfer coefficient and baseline heat transfer coefficient (h o,c /h o ), which in the work of Johnston, et al (1999) are between 1.3 and 1.5 in areas of curvature, where in Smith, et al (2000) this ratio is between 1.06 and 1.26. …”
Section: Transonic Turbine Blade Data -Holmberg 1996mentioning
confidence: 99%
“…As a comparison with this data, if the low, turbulence no film-cooling data on the suction surface (Table 3.1 and Smith, et al, 2000) is compared to the high turbulence, suction surface film cooling data in Table 3.10, the result would be a ratio (h t,c /h o ) of approximately 1.16-1.34. Johnston, et al (1999) reported data of this type for heat transfer data with film cooling and high freestream turbulence on a quarter cylinder model. They reported ratios as high as 1.6 on areas with curvature, which is significantly higher than the predicted data in the current work.…”
Section: Transonic Turbine Blade Data -Holmberg 1996mentioning
confidence: 99%